Development A Cultural Studies Reader - Schech, Susanne; Haggis, Jane (Blackwell Publishers Ltd, 2002)
Development studies has tended to neglect culture as a factor in development processes. This book of readings redresses the balance, gathering together some of the most influential contributions that reflect on the relationship between culture and development. It traces the evolution of the debate, from viewing culture simply as an attribute of societies undergoing development to exploring how development itself operates as a cultural process.